The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/separations10010051
|View full text |Cite
|
Sign up to set email alerts
|

SPME-GC-MS Analysis of the Volatile Profile of Three Fresh Yarrow (Achillea millefolium L.) Morphotypes from Different Regions of Northern Italy

Abstract: Achillea millefolium L. is the most representative plant of the genus Achillea due to its long-standing use. Previous investigations have allowed for the identification of many chemical compounds including phenols, flavonoids, monoterpenes, sesquiterpenes, and their derivatives. However, only a few reports have considered flower color in relation to A. millefolium composition. In this work, the phytochemical analysis on the volatile content of fresh samples of three morphotypes—white, pink and deep pink—collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Available literature data suggested that the white-flowered A. millefolium morphotype exhibited a different accumulation of certain compounds, such as flavonoids and essential oils, compared to its pink-flowered morphotype [32]. Garzoli et al found that the aerial parts of the pink morphotype A. millefolium accumulated higher amounts of monoterpenes than the white morphotype [33]. According to the authors, these differences in phytochemical composition between morphotypes suggested a potential adaptation to different ecological conditions or reproductive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Available literature data suggested that the white-flowered A. millefolium morphotype exhibited a different accumulation of certain compounds, such as flavonoids and essential oils, compared to its pink-flowered morphotype [32]. Garzoli et al found that the aerial parts of the pink morphotype A. millefolium accumulated higher amounts of monoterpenes than the white morphotype [33]. According to the authors, these differences in phytochemical composition between morphotypes suggested a potential adaptation to different ecological conditions or reproductive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…While there is relatively vast knowledge of the phytochemistry, biological activity, and applications of A. millefolium plants, the information on the structure of secretory tissues in this species and the location of bioactive substances is incomplete. The literature data also indicate that the content of bioactive compounds in yarrow raw material depends on the region of origin of the plant [56][57][58][59][60]. Therefore, the aim of the current study was (i) to present the structure of secretory tissues of Achillea millefolium subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Рослинні препарати деревію ефективно застосовують для лікування розладів менструального циклу, полегшення менструальних спазмів і болю, для зниження артеріального тиску, лікування інфекцій верхніх дихальних шляхів [1,[7][8][9]. Деякі сполуки, що містяться в ефірній олії, показали високий потенціал щодо руйнування активного центру протеаз і можуть бути застосовані в дослідженнях для виявлення ефективних засобів проти SARS-CoV [10].…”
unclassified
“…зумовлені наявністю в його траві та екстрактах широкого спектра натуральних компонентів. Найпоширенішими сполуками є флавоноїди, фенолкарбонові кислоти, терпени, фітостероли, органічні та жирні кислоти, дубильні речовини, кумарини, амінокислоти, полісахариди, саліцилова кислота, вітаміни С та К [2,4,7,8,[11][12][13].…”
unclassified
See 1 more Smart Citation